Knee Kinetics and Kinematics in Patients with Ankle Arthroplasty and Ankle Arthrodesis. Issue 3 (14th September 2018) - Roney, Andrew; Kraszewski, Andrew; Fansa, Ashraf; de Cesar Netto, Cesar; Ellis, Scott; Deland, Jonathan; Levine, David; Demetracopoulos, Constantine
Category: Ankle Arthritis Introduction/Purpose: Ankle arthritis is a debilitating problem, causing significant pain and functional limitations. Previous literature suggests patients treated with ankle arthroplasty (TAA) versus ankle arthrodesis (AA) may have better function and have lower risk for adjacent joint arthritis in the foot. However, there is little research on how these interventions impact proximal joints, such as the knee. The knee adduction moment (KAM) is a surrogate measure for the force experienced at the medial tibiofemoral compartment and is linked with the onset and progression of knee osteoarthritis. We hypothesized that patients with TAA and AA will exhibit altered frontal plane kinematics and kinetics in the affected limb compared to the contralateral unaffected side, and that the AA cohort will have a significantly greater KAM compared to TAA. Methods: Instrumented 3D walking gait was recorded in 10 TAA and 10 AA patients, minimum 2-year post-operatively. Subjects were demographically matched, had unilateral ankle arthritis and lacked complications such as adjacent joint arthritis, neuropathy or significant weight-bearing pain. The TAA patients had either a Salto-Talaris or INBONE prosthesis. Lower limb kinematic and kinetic data were measured with reflective skin surface markers and floor-embedded force plates at self-selected walking speeds. Average first and second peak KAMs [N-m/kg], KAM impulse [N-m-s/kg] and range-of-motion (ROM, [°]) were calculated on both the affected and unaffected limb for each patient. Group differences in KAM, impulse and ROM between TAA and AA interventions and the affected and unaffected limb were analyzed using a 2-sample unpaired t test. P-values less than 0.05 were considered significant. Results: See Table 1 for demographic and statistical analyses summary. Between the affected and unaffected limbs in each surgical cohort there were no significant differences in the KAM's first and second peak or impulse (p>0.135) and no difference in the knee ROM in any plane (p>0.214). When comparing AA with TAA, the average first peak KAMs generated while walking were 0.07N-m/kg greater in the TAA treatment but that difference was not significant (p=0.429). The second peak KAM was, on average, 0.1N-m/kg greater within TAA patients but was also not statistically different from AA patients (p=0.594). The KAM impulse and ROM in all 3 planes were not different between intervention types (p>0.318). Conclusion: TAA and AA may not significantly affect ipsilateral knee kinetics and KAMs in short term follow-up. This study highlights the importance of continuing to study these parameters in larger cohorts of patients with longer follow-up to determine how our treatment of end-stage ankle arthritis may affect the incidence or progression of ipsilateral knee osteoarthritis.